Development of the College of Science digital scholarship commons with an integrated scholar profile - Emano, Judy Ann M.; Dorado, Dan Anthony D.; Perez, Paul Jason V. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2022)
The delicate and sensitive nature of science information is crucial, its organization and management is paramount; therefore, a good research data management (RDM) service necessary. RDM service helps researchers and faculty members save time, increase citations enhance reproducibility, preserve data, increase visibility to founding agencies, and networking (Miller, Miller & Phillips,2018). While RDM is becoming relevant and gaining a huge recognition within the scholarly community, understanding the research activities of the CS faculty and researchers were greatly help in the governance of the large amounts of research data produced by the college. The essential role of academic libraries involves its expertise in handling and managing data, because libraries are now actively involved in research data services that address the entire research data lifecycle (Frederick, 2019). Therefore, this project aims to develop an in-house institutional repository (IR) service for the University of the Philippines Diliman College of Science. This is an RDM service that offer the College of Science (CS) faculty and researches a platform to store, manage and share their scholarly works. Additionally, this IR is also for archiving, reusing and repurposing. To maintain the relevance and sustainability of the IR, managing and preserving digital data and making sure that data is stored efficiently and discoverable by our identified stakeholders and most specially utilized with confidence through authenticity and integrity (Miller et al., 2018).

A survey was conducted to gather initial information from the faculty and researchers in the College of Science (CS) about their research data concerns and issues which is lack of repository to organize and store large bulk of data. In terms storage, 90% of all survey participants store their data in their personal PC or laptop, laboratory PC, cloud storage like Google Driver or iCloud, hard drives or flash drives only that are not even searchable by others.

The entirety of the project was expected to be completed in eight (8) phases: Idea or project initiation that involved defining the need, goals and meeting stakeholders (identifying key person decision makers, defining committee members and their responsibilities, creating project plan documentation (identify deliverables and timelines). establishing /forming the Institutional Repository Committee Network (IRCN) (actual members) and creating a detailed project plan and team member’s responsibilities and goals; gather and document requirements (surveys, interview, data gathering, and communication with project host); high-level design included defining content, defining feature set, creating metadata schema, defining access protocols, defining maintenance process, and choosing a tool); Development (develop system and create prototypes); Testing (conduct system testing); Perform User Acceptance Testing (using prototypes); Fix systems as needed (create final system); and lastly, Launch system (final project).

The 7-month duration of this project was successful because objectives are met and delivered to the project sponsor. However, the remaining phases in the development of the IR until its official launch will still be implemented after this project; and the project manager will continue to monitor and facilitate the completion of this IR.
Special Problem
Keywords: Research -- Information services; Communication in learning and scholarship